The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.molcel.2007.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Scm3 Is Essential to Recruit the Histone H3 Variant Cse4 to Centromeres and to Maintain a Functional Kinetochore

Abstract: The kinetochore is a complex multiprotein structure located at centromeres that is essential for proper chromosome segregation. Budding-yeast Cse4 is an essential evolutionarily conserved histone H3 variant recruited to the centromere by an unknown mechanism. We have identified Scm3, an inner kinetochore protein that immunopurifies with Cse4. Scm3 is essential for viability and localizes to all centromeres. Construction of a conditional SCM3 allele reveals that depletion results in metaphase arrest, with dupli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
241
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(254 citation statements)
references
References 44 publications
13
241
0
Order By: Relevance
“…With a single centromeric nucleosome, one way budding yeast could establish CEN identity each cell division would be to prevent canonical H3 from being deposited at CENs. Aside from one discrepancy (20), recent data have shown that canonical H3 is capable of assembling into a nucleosome over the CEN-determining elements (21,22), an observation that we have also made (S.F. and S.B., unpublished data).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…With a single centromeric nucleosome, one way budding yeast could establish CEN identity each cell division would be to prevent canonical H3 from being deposited at CENs. Aside from one discrepancy (20), recent data have shown that canonical H3 is capable of assembling into a nucleosome over the CEN-determining elements (21,22), an observation that we have also made (S.F. and S.B., unpublished data).…”
Section: Discussionsupporting
confidence: 81%
“…28 and 29). Yet, DNA sequence alone seems insufficient to ensure proper Cse4 localization because distinct KT proteins are essential for Cse4 localization (22,30,31). Consistent with this, KT proteins are also required for CenH3 localization in multicellular eukaryotes (32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 88%
“…It is distantly related to the yeast centromeric protein Scm3 (Camahort et al 2007;Mizuguchi et al 2007;Stoler et al 2007;Sanchez-Pulido et al 2009). HJURP interacts directly with CENP-A and histone H4, localizes CENP-A to the centromere in a cell cycle-dependent manner, and enables the deposition of newly synthesized CENP-A into the centromeric nucleosome.…”
mentioning
confidence: 99%
“…The human proteins hMis18 and M18BP1, recruited to centromere at telophase-G1, and RbAp46/RbAp48 may act to prime centromere for CENP-A localization (21). In S. cerivisiae and S. pombe, Scm3 (Suppressor of chromosome mis-segregation 3) protein was shown to specifically bind the CenH3-H4 complex and to be required for its assembly into the centromeric chromatin (22)(23)(24)(25)(26).…”
mentioning
confidence: 99%